Bioactive components of commiphora gileadensis plant for various medicinal applications: A bibliometric analysis - Mokaizh, A. A.; Nour, A. H.; Alara, Oluwaseun R.; Baarimah, Abdullah O. (IEEE, 2022)
Herbal medicine is becoming increasingly popular all over the world. As an alternative to currently used antibiotics, there is a need to find naturally occurring substances from plants that contain bioactive components. Commiphora gileadensis is a significant medicinal plant that has been used historically and, in the future, where this tree species is important economically and medicinally. The medicinal potential of C. gileadensis stems from the presence of secondary phytoconstituents, which perform a variety of functions including antioxidant, antimicrobial, cytotoxic, anticancer, and antiviral. Several studies have been conducted to integrate the ecological and biological properties of C. gileadensis. However, no scientometric analysis has been attempted to investigate the holistic understanding of the plant. The study’s aim is to perform a bibliometric analysis of the plant literature on C. gileadensis and present a summary of research development from 2010 to September 2022. 40 documents were pulled from the Scopus database. To display the literature by country, scientific journal, and keyword, the VOSviewer tool was employed. The findings revealed that “Antibacterial,” “Antioxidant,” “Anti-microbial,” “Anticancer,” and “Sustainable Medicinal Plant” have recently risen to prominence as mainstream topics associated with this field, piqued the interest of academics, and may represent future research opportunities. Furthermore, based on the most keywords frequently utilized, seven important research domains linked with C. Gileadensis have been identified, including “Balm of Gilead”, “Balm of Judea”, “Apharsemon”, “Opobalsamum”, “Mecca Balsam”, “Besham (Becham)” and “Myrrha”. As a result, explanations for research findings and recommendations for future studies on the integration of C. Gileadensis usage and its valuable bioactive components for multi-Medicinal applications have been provided.